PEMETAAN ANALOGI PADA KONSEP ABSTRAK FISIKA - Suseno, Nyoto (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The research of any where founded majority students have common difficulties in abstract physics concept. The result of observation, lecturers have problemÂ in teaching implementation of abstract concepts on physics learning. The objective of this research is to find out the ways how to overcome this problem. The research place ofÂ physics education programs and senior high school. The data are colected by quetionere, observation and interview. The lecturer behavior to making out this case is use of analogy to make concrete a abstract concept. This action is true, because the analogies are dynamic tools that facilitate understanding, rather than representations of the correct and static explanations. Using analogies not only promoted profound understanding of abstract concept, but also helped students overcome their misconceptions. However used analogy in teaching not yet planed with seriousness, analogy used spontanously with the result that less optimal. By planing and selecting right analogy, the role of analogy can be achieved the optimal result. Therefore, it is important to maping analogies of abstract consepts on physics learning.